Green Human Resource Management and Employee Eco-Behaviour in Eco-Resorts: Testing the Mediating Role of Organisational Environmental Culture - Andih, Deisy Christina; Karnawati, Hennidah (Journal of Tourism, Hospitality and Travel Management, 2026)
This study investigates the complex structural and psychological mechanisms that translate Green Human Resource Management (GHRM) into employee eco-behavior and organizational environmental performance within eco-resorts. Grounded in the Ability-Motivation-Opportunity (AMO) framework and Affective Events Theory, this research proposes and tests a dual-path sequential mediation model. Utilizing a quantitative cross-sectional design, data collected from 350 full-time eco-resort employees were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results confirm that GHRM acts as a robust catalyst, significantly enhancing both organizational environmental culture and green human capital. Crucially, the findings reveal that GHRM exerts no direct effect on environmental passion, indicating that formal HR policies are emotionally sterile in isolation. Instead, affective activation requires full mediation; passion is only ignited through a supportive green culture and the cognitive empowerment of human capital. Ultimately, this sequential transmission—from HR policies to culture, capability, passion, and behavior—significantly elevates macro-level environmental performance. This study provides critical insights for regenerative tourism, demonstrating that environmental excellence requires holistically engineering an organization's cultural and cognitive ecosystem.